2005
DOI: 10.1645/ge-3456rn.1
|View full text |Cite
|
Sign up to set email alerts
|

Diphyllobothrium: Neolithic Parasite?

Abstract: During paleoparasitological analyses on several Neolithic sites in Switzerland (Arbon-Bleiche 3) and southwestern Germany (Hornstaad-Hörnle I, Torwiesen II, and Seekirch-Stockwiesen), numerous eggs of Diphyllobothrium sp. were recovered. This is one of the earliest occurrences of this parasite during the prehistoric period in the Old World. The prevalence of this helminth in the samples studied raises the question as to how important parasitic diseases were during the Neolithic period and what their actual con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Eggs of the fish tapeworms Diphyllobothrium spp have been described in archaeological contexts in Peru, Chile, the US, France, Germany, Switzerland, and Israel (Le Bailly et al . ). Diphyllobothrium 's definitive hosts include humans, with fish serving as second intermediate hosts.…”
Section: Archaeo‐ and Paleoparasitologymentioning
confidence: 97%
“…Eggs of the fish tapeworms Diphyllobothrium spp have been described in archaeological contexts in Peru, Chile, the US, France, Germany, Switzerland, and Israel (Le Bailly et al . ). Diphyllobothrium 's definitive hosts include humans, with fish serving as second intermediate hosts.…”
Section: Archaeo‐ and Paleoparasitologymentioning
confidence: 97%
“…Surprisingly, no fish parasites were found in the sample although it is likely that this population was exposed to this type of infection. Fish is an important source of protein in waterside settled populations and multiple paleoparasitological studies have reported infection of human population with fish parasites in Europe (Le Bailly et al 2005Bailly et al , 2007, America (Araújo et al 2011) andAsia (Han et al 2003;Matsui and Kanehara 2003;Seo et al 2008). The 9 absence of fish parasites may be related to food habits of this population since cooking of fish and seafood kills parasites that may be present.…”
Section: Discussionmentioning
confidence: 99%
“…Since the earliest paleoparasitological studies, Ascaris eggs have been found in archaeological samples, especially in Europe (Taylor 1955, Pike 1967, Greig 1981, Jones et al 1988, Bouchet 1991, 1993, 1995, Bouchet & Paicheler 1995, Bouchet et al 1996, 1998, Rousset et al 1996, Fernandes et al 2005, Le Bailly et al 2005. At archaeological sites of South America, Ascaris sp.…”
Section: Discussionmentioning
confidence: 99%